Randomised, double-blind trial on the value of tapered discontinuation of clopidogrel maintenance therapy after drug-eluting stent implantation - Fiedler, K. Anette; Mehilli, Julinda; Kufner, Sebastian; Schlichting, Anna; Ibrahim, Tareq; Sibbing, Dirk; Ott, Ilka; Schunkert, Heribert; Laugwitz, Karl-Ludwig; Kastrati, Adnan; Schulz, Stefanie (Thrombosis and Haemostasis, 2013)
There is little evidence on the optimal mode of clopidogrel discontinuation. Epidemiological studies observed clustering of thrombotic events after cessation of chronic clopidogrel therapy. The underlying mechanism has been ascribed to transient platelet hyper-reactivity. Gradual tapering of clopidogrel may have the potential to attenuate this phenomenon. The objective of the present study was to assess whether in patients with drug-eluting stents (DES) gradual discontinuation of clopidogrel maintenance therapy is superior to conventional, abrupt discontinuation. Patients with planned discontinuation of chronic clopidogrel therapy after DES implantation were randomised in a double-blinded fashion to either gradual discontinuation (according to a tapering schema over four weeks) or abrupt discontinuation (after continued clopidogrel therapy for additional four weeks). The primary endpoint was the composite of cardiac death, myocardial infarction, stroke, stent thrombosis, major bleeding or rehospitalisation due to an acute coronary syndrome at 90 days. Enrollment of 3,000 patients was planned. The study was stopped prematurely due to slow recruitment after enrollment of 782 patients. At 90 days, nine of 392 patients (2.3%) with tapered cessation reached the primary endpoint compared to five of 390 patients (1.3%) with abrupt cessation (p=0.284). The composite of death or myocardial infarction occurred in three patients with tapered and three patients with abrupt discontinuation (p=0.764). In conclusion, tapered discontinuation of chronic clopidogrel therapy is not superior to abrupt discontinuation regarding the primary endpoint in this study. However, the results must be interpreted in view of the premature termination of the trial and low event rates. © Schattauer 2014.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Clopidogrel; Drug-eluting stent; Rebound; Tapering